Over there - U.S. Navy. - Sterner, Albert, 1863-1946:::Creator:::::::::::: (N. Y. : American Lithographic Co.)
Naval recruitment poster depicting a battle ready Columbia pointing the way for a sailor with her right hand while her left hand rests on a sword. The sailor is holding onto a flag pole while the flag waves amid a stormy atmosphere. A row of battleships is seen in the background.